Social services, human capital, and technical efficiency of smallholders in Burkina Faso - Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2011)
This study applies regression analysis as well as a non-parametric method to survey data from Burkina Faso to analyze the role of human capital in explaining technical efficiency in smallholder agricultural production. Exploiting the panel nature of the data and explicitly treating human capital inputs as endogenous, a two-stage estimation method is used for the analysis of determinants of data envelopment analysis (DEA) technical efficiency scores in a double-bootstrap procedure. Findings suggest that the impact of human capital on technical efficiency differs strongly by gender. Strong positive returns exist for education of females, whereas male education is associated with higher inefficiency. Body mass index of adult females also positively relates to technical efficiency. At the community level, presence of a clinic, connection to the electrical grid, presence of a secondary school, and year-round accessibility of the community are found to be vital for human capital formation.